2020
DOI: 10.1155/2020/4827617
|View full text |Cite
|
Sign up to set email alerts
|

Skin Closure Tape and Surgical Staples in Primary Total Knee Arthroplasty: A Systematic Review and Meta-Analysis

Abstract: Background. Staples closure technology has been widely used in total knee arthroplasty (TKA) and achieved good results. In recent years, a new type of material called skin closure tape (SCT) has been applied to TKA which also showed good treatment results. However, since it is still not clear yet which one is better, this paper collects literatures for statistical analysis so as to provide evidence for the use of SCT in TKA. Methods. The comparative study on effects between SCT and staples is reviewed after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…e total knee arthroplasty is a new technique for treating knee joint diseases developed gradually after the successful application of artificial hip joint [17][18][19]. Zhong et al [20] studied mirabilite after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…e total knee arthroplasty is a new technique for treating knee joint diseases developed gradually after the successful application of artificial hip joint [17][18][19]. Zhong et al [20] studied mirabilite after TKA.…”
Section: Introductionmentioning
confidence: 99%
“…In this analysis of studies, we found that zip-type SCD compared with surgical staples decrease wound pain evaluation, wound scar score, and readmission. Our meta-analysis was more systematic, comprehensive, and novel than the previous meta-analysis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%